Research on ignition criterion and combustion behavior of aluminum alloy for lithium battery - Xiuping Ding; Xi Wang; Chenhui Zhu; JinMeng Hu; Minheng Xu; Minyu Ma; Jinfeng Huang (Scientific Reports)
Abstract Thermal runaway represents a critical factor of catastrophic failure in power battery systems, posing significant safety risks in electric vehicle applications. Aluminum alloy casings serve as a primary protective barrier, and comprehensive investigation of their combustion characteristics is crucial for mitigating potential safety hazards in lithium-ion battery systems. The present study systematically examines the influence of dimensional variations and flame-retardant Ni-based surface modifications on the combustion mechanisms of 5052 aluminum alloy employed in lithium-ion battery configurations. Experimental findings reveal that the ignition temperature of the aluminum alloy decreased with oxygen pressure increased. The application of Ni-based flame-retardant coating markedly increasing the ignition threshold to 1007.8 ± 18.8 K. A robust predictive model characterizing the combustion threshold of the aluminum alloy and its flame-resistant coating was developed, demonstrating exceptional statistical validity with R2 values consistently exceeding 0.95. Microscopic morphological analysis of the combustion zones revealed that the incorporation of flame-retardant coating facilitates the formation of a more comprehensive oxide film and denser solidification zone microstructure.